Arquitectura bananera, degradación ambiental, e imágenes de violencia espacial en el Caribe costarricense - Solano-Meza, Natalia (2023)
This article explores the interrelations between environmental degradation, the expansion of the banana monoculture, and specific architectural and spatial configurations produced by the United Fruit Company in the Costa Rican Caribbean. The notion of “spatial violence” is used to examine images that reveal a history of ecological devastation and racial segregation fostered by the banana corporations, materialized in the organization of space.